P476 Monitoring antifungal resistance in a global collection of Candida spp. surveillance isolates, including C. auris—analysis of resistance in antifungals (ARIA) 2020 study. (20th September 2022) - Kothari, Nimmi; Hawser, Stephen; Olari, Sara; Sartori, Silvia; Mathur, Tarun
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objectives: Analysis of resistance in antifungals (ARIA) is a recent longitudinal global surveillance initiative collecting yeast and fungal isolates from hospitals worldwide designed to determine susceptibility profiles and monitor the resistance trends among antifungal agents. ARIA reports the susceptibility patterns of data concerning echinocandins, second-generation triazoles, and fluconazole against clinical Candida spp., and filamentous fungal isolates from worldwide sources. Methods: Candida spp. isolates ( n = 662) were collected from hospitals worldwide during 2020 from 13 different sites—Argentina ( n = 1), Australia ( n = 2), Germany ( n = 1), India ( n = 2), Italy ( n = 1), Panama ( n = 1), Spain ( n = 1), Turkey ( n = 1), United Kingdom ( n = 1), and United States ( n = 2). These isolates were shipped to a central laboratory at IHMA Europe, Switzerland, and re-identified by MALDI-TOF or molecular methods. The MICs were performed by broth microdilution method in line with CLSI susceptibility testing standards—CLSI M27-A4 and M38-A2—methodologies and percentage susceptibility (%S) were calculated. Antifungals tested were amphotericin B (AMB), anidulafungin (ANID), fluconazole (FLU), isavuconazole (ISA), caspofungin (CASP), micafungin (MIC), posaconazole (POS), and voriconazole (VOR). Results: Table 1: Summary MIC and susceptibility data of Candida spp. isolates for all countries combined Conclusions: The data from the ARIA 2020 study indicate that overall antifungal resistance is low among the Candida spp. isolates except for C. glabrata and C. krusei where resistance to one or more antifungal agents was observed. However, there was no significant difference in susceptibility pattern was observed when susceptibility data of C. glabrata and C. krusei from different continents were compared. The emergence of resistance was evident among C. auris isolates as they have shown reduced susceptibility to azoles in this study. Antifungal resistance surveillance and investigation into resistance mechanisms are of paramount importance. The ongoing ARIA surveillance study will provide resources to monitor antifungal resistance trends, provide key information to caregivers and provide essential information with respect to the development of novel antifungal agents.